Tobacco use results in inferior outcomes after anatomic total shoulder arthroplasty. Issue 1 (January 2019) - Walters, Jordan D.; George, L. Watson; Wan, Jim Y.; Brolin, Tyler J.; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Background: This study examined the effect of tobacco use on outcomes of primary anatomic total shoulder arthroplasty (TSA). Methods: A retrospective search identified 59 nonsmokers, 29 former smokers, and 14 current smokers with primary anatomic TSA and at least 2 yr of follow-up. At mean follow-up of 3 yr, patients were assessed with a visual analog scale (VAS), American Shoulder and Elbow Surgeons (ASES), and Single Assessment Numeric Evaluation (SANE) scores and range-of-motion testing. Results: Smokers were significantly younger than nonsmokers or former smokers; there were no other statistically significant differences. VAS scores were significantly higher in current smokers and ASES scores were significantly lower. Complication rates were 36% in current smokers, 15% in nonsmokers, and 7% in former smokers ( P = 0.05). Conclusions: Current smokers had significantly worse pain and functional scores and more complications. Former smokers had results similar to nonsmokers, suggesting improved outcomes are possible in patients who quit smoking preoperatively.